The Problem of Latin American Integration: Why Are the Objectives Not Being Fulfilled? An Analysis of the Andean Community - Cantos, Gabriel (2025)
The Andean Community is one of the oldest international organizations in the region, which has focused its objectives, mainly on the economic development of the bloc’s member countries. However, and in spite of the bloc’s constant efforts to meet all of its behind-the-scenes objectives, the CAN appears to be destined to function at half its capabilities and to fail in achieving its objectives. In this sense, this essay aims to study why CAN objectives are not being fulfilled. Based on this, the article will try to unveil this question through a historical analysis of the integration process in Latin America. Later, it will study the CAN integration process, and finally it will analyze the factors that lead to the integration process does not manage to meet the objectives that have been set. In thissense, it is understood that the main reasons why the project fails are: 1. due to the lack of will of the Member States; 2. a cause of ideological disputes that are diametrically opposed between members; and 3. due to the lack of strong leadership in the integration process.